GENDER DIFFERENCES IN COMPUTER LITERACY AMONG UNDERGRADUATE STUDENTS AT THE UNIVERSITY OF BOTSWANA: IMPLICATIONS FOR LIBRARY USE - Tella, Adeyinka; S.M., Mutula (Malaysian Journal of Library and Information Science, 2008)
This paper, presents findings of a study that was carried out in January 2006 at the University of Botswana to determine gender differences amongst undergraduates’ students across all disciplines with regard to computer literacy. Five hundred students were surveyed of which 300 were females while 200 were male. The proportion of female to male students at the University of Botswana is 53%:47%. Purposive sampling was used to select respondents from the six faculties of the University; a survey questionnaire was administered to them and collected on its completion. Descriptive statistics and t-test were employed in the analysis of data. The results suggest that gender differences exist between female and male undergraduate students at the University of Botswana with regard to computer literacy. The findings further revealed that students with higher computer literacy were more inclined to access and make use of library facilities. Moreover, differences exist in the respondents’ computer usage and software application. The paper discusses the implications of these results on the students’ use of library.